2014
DOI: 10.7773/cm.v40i1.2318
|View full text |Cite
|
Sign up to set email alerts
|

Cu, Pb, and Zn content in sediments and benthic organisms from San Jorge Bay (northern Chile): Accumulation and biotransference in subtidal coastal systems

Abstract: The concentration of Cu, Pb, and Zn was measured in order to evaluate their sediment enrichment and probable biomagnification trends in benthic trophic chains of the coastal zone of San Jorge Bay (northern Chile). The mean concentrations of Cu, Zn, and Pb were 103.6, 72.6, and 38.6 mg kg-1 , respectively, in sediments and 28.3, 32.5, and 21.9 mg kg-1 , respectively, in organisms. The geoaccumulation index indicated that sectors with industrial activities show some degree of metal enrichment; however, Zn and Pb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 34 publications
(91 reference statements)
0
9
0
4
Order By: Relevance
“…Conversely, EFs obtained for As, Cd, Cu, Mo, Pb, and Zn were generally greater than 20, indicating that their sources cannot be from rocks and soil present in the city ( Table 5 ). To support this conclusion, other studies conducted in marine environments of the Bay of Antofagasta have showed that enrichment of metals such as Cu, Pb, and Zn in coastal waters, bottom sediments, and benthic organisms are related to industrial activities developed along the coastal border of the bay ( Salamanca et al, 2000 ; Lépez, Furet & Aracena, 2001 ; Salamanca, Jara & Rodríguez, 2004 ; Valdés et al, 2010 , 2011 , 2014 , 2015 ; Calderón & Valdés, 2012 ).…”
Section: Discussionmentioning
confidence: 83%
“…Conversely, EFs obtained for As, Cd, Cu, Mo, Pb, and Zn were generally greater than 20, indicating that their sources cannot be from rocks and soil present in the city ( Table 5 ). To support this conclusion, other studies conducted in marine environments of the Bay of Antofagasta have showed that enrichment of metals such as Cu, Pb, and Zn in coastal waters, bottom sediments, and benthic organisms are related to industrial activities developed along the coastal border of the bay ( Salamanca et al, 2000 ; Lépez, Furet & Aracena, 2001 ; Salamanca, Jara & Rodríguez, 2004 ; Valdés et al, 2010 , 2011 , 2014 , 2015 ; Calderón & Valdés, 2012 ).…”
Section: Discussionmentioning
confidence: 83%
“…Las principales actividades económicas de Sinaloa dependen de abundates recursos hídricos y de la calidad del agua (CONAPESCA 2012). Hoy en día se conoce que el agua contaminada de los canales de drenaje agrícola afecta de manera negativa la vida acuática y terrestre en Sinaloa (Escobedo-Urías et al 1999, Haws et al 2006, Ochoa Izaguirre y Soto-Jiménez 2013), México y el mundo (Bagordo et al 2012, Matano et al 2013, Riera et al 2013, Valdés et al 2014, Wu et al 2014. Por otra parte, los canales de drenaje pueden funcionar como humedales artificiales de flujo superficial y disminuir la contaminación del agua y sus efectos negativos, pero éstos deben transportar bajos flujos de agua para favorecer el establecimiento de las plantas acuáticas (Kadlec y Wallace 2009).…”
Section: Water Sampling and Analysisunclassified
“…Fecal coliforms, found in the intestine and feces of animals, are indicators of pollution and consequently of water quality, and thus warn about the possible presence of human pathogens. The presence of fecal coliforms in aquatic environments may be due to the abundant incorporation of water contaminated by sewage and other organic wastes from anthropogenic activities (Cupul-Magaña et al 2006, Bagordo et al 2012, Sidhu et al 2012, Barrera-Escorcia et al 2013, Ochoa-Izaguirre and Soto-Jiménez 2013, Valdés et al 2014, Wu et al 2014.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations